Comparative study on management of diabetic ulcer with platelet-rich plasma and conventional dressing - Dhanasekaran, Uma; Arumugam, Ramesh; Jayasubramaniyar, Latha (International Surgery Journal, 2020)
Background: About 15% of diabetic patients will develop a chronic ulcer, and about 25% of those will have to undergo foot amputation. Despite evidence of the effectiveness of autologous protein C (PC) in diabetic ulcers, efficacy and feasibility of this treatment in the general population remain unclear. Aim of the study was to compare the efficiency of management of diabetic ulcer with platelet-rich plasma (PRP) and conventional dressing. Methods: A total of 40 patients who divided into two groups: group I comprising 20 patients received homologous platelet concentrate and group II comprising 20 patients received conventional wound dressing, and the results had statistically discussed. Results: Out of total 40 patients, 20 received homologous platelet dressings, and the 20 patients received conventional moist wound dressings. 7 patients had operated for split skin grafting, 7 patients had 0-10% of the area covered with necrotic tissue, mean duration of hospital stay was 18 days, mean duration of wound debridement was 3 days and mean number of wound dressing was 6. In conventional wound dressing group, 15 patients had operated for split skin grafting, 4 patients had 0-10% of the area covered with necrotic tissue, mean duration of hospital stay was 39 days, mean duration of wound debridement was 18 days and mean number of wound dressing was 48. Conclusions: Patients operated for split skin grafting, number of wound debridement, duration of hospital stay, and duration of wound debridement, necrotic tissue coverage was less in platelet group compared to the conventional wound dressing.